Prevalence and risk factors of developing cardiac arrhythmia in patients presenting to the emergency department with electrical injuries - Ramiz Yazıcı; Bensu Bulut; Murat Genç; Medine Akkan Öz; Serkan Şahin; Ayşenur Gür; Hüseyin Mutlu (PLoS ONE, 2025)
Background Cardiac arrhythmias following electrical shocks are significant concerns in emergency medicine, yet predictive factors remain unclear. Objective This study aimed to investigate the prevalence and risk factors of cardiac arrhythmias in patients presenting with electrical injuries to the emergency department. Methods In this retrospective study conducted between January 2019 and December 2023, we analysed 189 patients aged ≥18 years who presented with electrical injuries. Patients were divided into two groups based on whether or not they developed an arrhythmia. Demographics, clinical characteristics, and laboratory parameters were compared between groups. Results Cardiac arrhythmia developed in 21.2% (n = 40) of patients. The arrhythmia group showed significantly higher mean age (32.4 ± 16.7 vs 26.5 ± 14.8 years, p = 0.023) and high-voltage exposure rates (≥1000 V) (p = 0.015). Multivariate analysis identified age (OR: 1.02, 95% CI: 1.01–1.05), CK > 850 U/L (OR: 1.32, 95% CI: 1.17–1.81), troponin >250 ng/mL (OR: 1.23, 95% CI: 1.09–1.72), lactate >2.1 mmol/L (OR: 2.51, 95% CI: 1.67–5.91), and high voltage (OR: 2.03, 95% CI: 1.64–5.39) as independent risk factors. ROC analysis showed high voltage (AUC: 0.804) as the strongest predictor of developing arrhythmia. Conclusion This study demonstrates that high voltage exposure, advanced age, and elevated biomarkers are significant predictors of developing arrhythmia in patients with electrical injuries. These findings may guide clinical decision-making regarding cardiac monitoring in the emergency department.